2016
DOI: 10.1037/ipp0000059
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Identity and Environmental Values: Do Spirituality and Political Consciousness Predict Environmental Regard Among Māori?

Abstract: Indigenous peoples often have a unique and deep connection to the land. However, quantitative research exploring this issue is scarce. The current research investigates cultural variation in environmental regard in New Zealand, where more recent settler groups have questioned the strength of Indigenous environmental regard. Study 1 examined differences in environmental regard held by Indigenous and non-Indigenous ethnic groups in a nationally representative data set, the New Zealand Attitudes and Values Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…Given that socio-political consciousness fosters a protective attitude toward the environment amongst Māori (Cowie et al 2016), we predicted that Māori socio-political consciousness would correlate positively with valuing environmental protection. Conversely, we expected that Māori spirituality, an aspect of identity that emphasises people as descendants of Papatūānuku (the Earth mother; Dell 2017), would correlate positively with valuing unity with nature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that socio-political consciousness fosters a protective attitude toward the environment amongst Māori (Cowie et al 2016), we predicted that Māori socio-political consciousness would correlate positively with valuing environmental protection. Conversely, we expected that Māori spirituality, an aspect of identity that emphasises people as descendants of Papatūānuku (the Earth mother; Dell 2017), would correlate positively with valuing unity with nature.…”
Section: Resultsmentioning
confidence: 99%
“…Given the importance of land, a vital aspect of tino rangatiratanga is the responsibility of Māori for the environment. As noted by Cowie et al (2016), Māori, connected by whakapapa to Papatūānuku, identify as tangata whenua (people of the land), a role recognised within New Zealand legislation. In this role, Māori are protected and sustained by the land, but are expected to reciprocate in turn-an obligation best exemplified by kaitiakitanga (guardianship/resource management; Kawharu 2000, p. 351).…”
Section: Māori Identity and Environmental Regardmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that Native American children were significantly more interested in playing with the diorama than playing with the toy animals, and were more likely than non-Native American children to engage in perspective taking within nature environment (Washinawatok et al, 2017). In a similar line of research, Cowie et al (2016) examined the environmental values of indigenous people's (Maori) in New Zealand. They found that the Maori people expressed higher levels of environmental values than European New Zealanders partially due to Maori people's high sociopolitical consciousness.…”
Section: Considering Diverse Cultural Orientations In the Usmentioning
confidence: 99%
“…Addressing these problems requires international, collective efforts, necessitating a better understanding of environmental beliefs and behaviors in all cultures. While there has been a substantial body of literature on environmental beliefs and behaviors (see Bamberg & Moser, 2007;Hines, Hungerford, & Tomera, 1987 for meta-analyses), cross-cultural research in this area, particularly comparisons between indigenous vs. non-indigenous peoples, remains limited (see Cowie, Greaves, Milfont, Houkamau, & Sibley, 2016). In light of this limitation, the current study was designed to conduct a comparison of the environmental beliefs and behaviors between an indigenous and a non-indigenous sample from New Zealand (NZ) and the US.…”
Section: Introductionmentioning
confidence: 99%